Reading in the Postgenomic Age: On Contemporary Literature and the Good Bionarrative Citizen. (29th June 2020) - Larkin, Lesley
Abstract: The "postgenomic age, " whose start date roughly corresponds to the turn of the millennium, is characterized not only by the rapid development of genomic technologies and commercial products but also by the widespread publication of literary works focused on genomics and its cultural implications. Defining "postgenomic literature" as literature that is both of and about the postgenomic age, this essay explores how works by nonfiction writer Rebecca Skloot and novelist Richard Powers exemplify a significant trend within the genre: the thematic exploration of ethical questions in the field of literature itself. While both authors address questions of medical and scientific ethics prompted by genomic research, with special emphasis on the exploitation of vulnerable populations, these questions lead readers directly to questions of narrative responsibility: who can tell whose story to whom—and for whose benefit? The Immortal Life of Henrietta Lacks and Generosity: An Enhancement, like other examples of postgenomic literature, invite readers to engage in critical reading practices that resist both textual and genetic determinism .